Determination of Growth Efficiency of Expansionary Fiscal Policy via Monetary Policy in Shrinking Periods: Wide Range of Country Analysis - Tugba Demirtas (An Overview on Business, Management and Economics Research Vol. 8, 2024)
There are many different opinions in the literature that expansionary fiscal policies can be effective on growth during periods of economic contraction. In this study, the effectiveness of fiscal policy is included in empirical analysis both in theory and practice, while the results of its interaction with monetary policy are also included. This study examines different approaches to expansionary fiscal policies regarding the effects and tradeoffs between fiscal expenditures-growth, expansionary tax policies-growth, and inflation-growth. The short-term and long- term effects of fiscal policies on growth in 110 countries for 2007-2016 were analyzed, considering the expansionary policies of the 2007-2009 period, the effect of the primary growth dynamics, and the interaction of monetary-fiscal policies. The results show a holistic view and effectiveness. When looking at the fiscal policies, only subsidies were found to be significant among the expenditure items in the short term, with a low probability. However, no positive relationship was found with growth. For this reason, it is observed that the fiscal policy composition discussed within the scope of the study is not pro-growth, and resources are inadequate or incorrectly transferred at the global level. It becomes clear that the common area of action in monetary policy supports growth and the importance of structural growth dynamics. Collaborating in fiscal and monetary policies among all countries may be more pro-growth. In the processes where growth was supported, inflation was reflected in the results where the trade-off was more limited.